2014
DOI: 10.1002/nmi2.53
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of representative clinical South African Staphylococcus aureus isolates from various clonal lineages

Abstract: Data concerning the virulence and pathogenesis of South African strains of Staphylococcus aureus are limited. We investigated host–pathogen interactions of randomly selected clinical S. aureus isolates representing various clones. We characterized the ability of isolates to adhere to fibronectin, fibrinogen, collagens IV and VI, to invade host cells and to induce cell death in vitro. We analysed the possible association of these results with characteristics such as methicillin resistance, Panton–Valentine leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Only three of the studied strains did not show the fnba gene [15, 24 and 72]. This is a high percentage (96.3%) of fnba-encoding genes but is in agreement with previous studies conducted in other African countries [52,53]. The high prevalence of α-haemolysin and fibronectin binding protein A is not unusual and could explain the high virulence of these infections, as they play a crucial role in colonisation and infection [16,24].…”
Section: Plos Onesupporting
confidence: 85%
“…Only three of the studied strains did not show the fnba gene [15, 24 and 72]. This is a high percentage (96.3%) of fnba-encoding genes but is in agreement with previous studies conducted in other African countries [52,53]. The high prevalence of α-haemolysin and fibronectin binding protein A is not unusual and could explain the high virulence of these infections, as they play a crucial role in colonisation and infection [16,24].…”
Section: Plos Onesupporting
confidence: 85%
“…Certain pandemic MRSA clones are spread worldwide. Recent publications describe the ST612-MRSA-IV clone (MLST CC8) as the most widespread MRSA clone in Cape Town, and South Africa (Jansen van Rensburg et al, 2011;Orth et al, 2013;Oosthuysen et al, 2013;Moodley et al, 2010). In this study ST 612 formed strong biofilms, which may contribute to its dominance in nosocomial infections in South Africa.…”
Section: Discussionmentioning
confidence: 69%
“…Pulsed-field gel electrophoresis (PFGE) is considered the reference standard for S. aureus strain typing and is the most discriminatory typing method (Deurenberg et al, 2007;Oosthuysen et al, 2013). The method described by McDougal et al was followed (McDougal et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the prevalence and diversity of clinical MRSA isolate in Pretoria, South Africa [ 4 , 5 ]. However, there are no reports on the distribution patterns of the multidrug efflux genes of the clinical isolates in South Africa.…”
Section: Introductionmentioning
confidence: 99%